STUDYING THE IMPACT OF RELIGIO-POLITICAL CONFRONTATIONS OF ISLAMIC EMPIRES IN KURDISTAN: FROM THE BEGINNING UNTIL THE END OF THE ISLAMIC CALIPHATE - Sabah Mofidi (Indonesian Journal of Islamic History and Culture, 2021)
This article seeks to address the problem of historiography and perspective in Middle East studies concerning dominated ethno-nations, especially the Kurds, while examining the religio-political confrontations between the Islamic empires and their significant socio-political consequences in Kurdistan through a historical study (primarily) based on secondary sources. With the dominance of the early Islamic Caliphate from the 7th century, the political powers of the Kurds’ ancestors were removed and the non-Muslim population severely declined. From the middle of the Abbasid Caliphate period (750-1258) Kurdish governments grew again. After the Abbasids, various Islamic sects gained power and Kurdistan gradually becoming the battlefield of various political powers. With the emergence of two empires, the Sunni Ottoman and Shiite Safavid (and its successors) in the 16th century, the internal conflicts in the Islamic world culminated and lasted until the early 20th century. Between the 7th and the early 20th century religio-political confrontations converging in Kurdistan have severely affected the land’s socio-political situation. This article examines how the Islamic empires used religion politically as a means to fight each other, as well as engage with the Kurdish revolts.